Experimental efficiency analysis of a solar panel electricity generation system using planar reflection - Duranay, Mehmet; Turmus, Ahmet; Tanyildizi, Vedat (Inst Engineering Technology-Iet, 2021)
Since energy consumption in all countries of the world is increasing day by day, the demand and interest on renewable energy resources are also increasing at the same rate. Using the current energy in the best way and searching for different energy sources have become an important field of study for countries. Studies on this area also continue in our country, which is lucky in terms of solar energy potential. In this experimental study, where the design and production stages were carried out interactively, the effect of reflected rays on the photovoltaic (PV) panel was observed and the comparison of reflected rays with direct rays was made. The system following the Sun and the system fixed at an appropriate angle was compared. Also, the theoretical and the experimental efficiency as a result of the experimental study of the movable and fixed system were calculated and compared for the direct and reflected radiation. The mechanism presented in this study allows more use of solar radiation by enhancing through reflection from surface-to-surface. With this experimental study more solar radiation will be provided with the panel placed on the back, in addition to the panel exposed to direct solar radiation. Thus, it will be possible to use double-faced panels for a solar tracking system.
Keywords: Photovoltaic Module; Collector